2019
DOI: 10.1371/journal.pone.0217305
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory dynamics of an electrically driven dissipative structure

Abstract: Physical systems open to a flow of energy can exhibit spontaneous symmetry breaking and self-organization. These nonequilibrium self-organized systems are known as dissipative structures. We study the oscillatory mode of an electrically driven dissipative structure. Our system consists of aluminum beads in shallow oil, which, when subjected to a high voltage, self-organize into connected ‘tree’ structures. The tree structures serve as pathways for the conduction of charge to ground. This system shows a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Function within dissipative structures is intrinsic, identifiable in their end-directed time evolution. Some dissipative structures (expanded on below) exhibit morphological and behavioral changes that drive the system to states of greater entropy production [ 25 , 26 , 27 , 30 , 31 , 32 ]. In our electrical dissipative structure, this manifests in an ‘energy-seeking’ behavior where tree-like structures of conducting spheres move through their environment, directed by electrical gradients, to regions of higher concentration of charges.…”
Section: Machines Dissipative Structures and Organismsmentioning
confidence: 99%
See 3 more Smart Citations
“…Function within dissipative structures is intrinsic, identifiable in their end-directed time evolution. Some dissipative structures (expanded on below) exhibit morphological and behavioral changes that drive the system to states of greater entropy production [ 25 , 26 , 27 , 30 , 31 , 32 ]. In our electrical dissipative structure, this manifests in an ‘energy-seeking’ behavior where tree-like structures of conducting spheres move through their environment, directed by electrical gradients, to regions of higher concentration of charges.…”
Section: Machines Dissipative Structures and Organismsmentioning
confidence: 99%
“…We have studied two dissipative structures, an electrical and a chemical system, which we classify as self-organized foraging implementations (SOFIs). Our electrical system (E-SOFI) produces an array of life-like properties, including foraging [ 25 , 26 , 27 , 31 ]), end-directed behavior [ 25 , 26 , 27 , 31 ], structure maintenance and self-healing [ 25 , 26 , 27 ], and even functional coordination [ 30 , 32 , 41 ]. The chemical system (C-SOFI) demonstrates flocking behavior [ 33 , 34 ] sensitivity to external thermal and magnetic fields [ 33 ], and collective navigation of environments [ 34 ].…”
Section: Bio-analogue Dissipative Structures: the Missing Linkmentioning
confidence: 99%
See 2 more Smart Citations
“…The system employed in the current study is a variation of a self-organizing electrical system reported in previous works [ 19 , 21 , 31 , 32 ]. The system consists of metal beads in shallow oil subject to a high electrical voltage.…”
Section: Introductionmentioning
confidence: 99%